Basic Contradiction in Religion - Nabil Nabil (STIT Al-Marhalah Al-Ulya Bekasi, 2018)
Contradiction provide insights into theoritical changes in perspective that lead to multi interpretation the law of contradiction contained unity of opposites in the religion is a fundamental law. And it turns out that there are contradiction in the basic religion of islam, namely syahadat as Ahmad Yulden Erwin in his writing, the contradiction are true and empty is the content.â€œNo god but Godâ€ if the phrase is to be written in symbolic logical language, it will be form into contradiction of proposition; -p á´§ p (which has wrong value). If the phrase is to be written in mathematic language, it will be form; -1 + 1 (which value 0). In other words, â€œsyahadatâ€ is a testimony of contradiction and emptiness. Accordingly the meaning, the phrase on a symbolically logical structure will be value wrong and or empty, except , if and if only. Logic can already prove that the contradiction are true and empty it was none other than content.Contradiction is the opposite of tautology, which is a form of statement that has only an example of a wrong substance, or a false statement in everything regardless of truth value of itâ€™s components.[1] To prove whether a statement is a contradiction, there are two ways to prove it. First is using a truth table, if all the options are F or false then they are called contradictions. The truth table of [( pâŸ¹Â q ) Ë„ p] Ë„ qÂ